KAJIAN PUSTAKA KETERTARIKAN GENERASI MUDA PADA SEKTOR PERTANIAN - I Gede Made Artha Sudewa Wijaya; Dumaris Priskila Purba (LPPM UNIVERSITAS KAHURIPAN KEDIRI, 2025)
Young people often avoid jobs in agriculture. The young farmer crisis has an impact on the use of technology to support sustainable agriculture. This study aims to explore young people's perceptions and interests in farming. The method involves a simple literature review using online sources like Google Scholar, ResearchGate, SpringerLink, EBSCO, Scopus, and Science Direct. Descriptive analysis is used to examine the data collected. The findings indicate that increasing young people's interest in agriculture can be achieved by improving the profession's image through educational guidance, modernization of technology, stable income guarantees, access to capital, training, and strengthening the sociocultural value of agricultural land. The roles of agricultural extension workers and family support are key in shaping positive perceptions and encouraging effective farmer renewal.